2020
DOI: 10.3390/ph13090250
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Multimodal Imaging Synthons for Chemoselective and Efficient Biomolecule Modification with Chelator and Near-Infrared Fluorescent Cyanine Dye

Abstract: The development of hybrid multimodal imaging synthons (MIS), carrying in addition to a chelator for radiometal labeling also a near-infrared (NIR) fluorescent cyanine dye was the aim of this work. The MIS should be introducible into biomolecules of choice via an efficient and chemoselective click chemistry reaction. After chemical optimization, a successful synthetic strategy towards such hybrid MIS was developed, based on solid phase-based synthesis techniques and applying different near-infrared fluorescent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 31 publications
6
18
0
Order By: Relevance
“…This conclusion is supported by the GRPR affinity datat hat were obtained for the ICG-comprising bioconjugates CC1-CC3 and the reference compounds CC4 and CC5 [25] :A lso within the group of ICG-comprising bioconjugates CC1-CC3,astrong correlationb etween the number of negative charges of the respectived ye molecule and GRPR affinity decrease was observed, going from CC1 (27.39 AE 2.01 nm;o ne negative charge on the ICG dye) over CC2 (56.07 AE 1.47 nm;t wo negative charges) to CC3 (181.23 AE 2.24 nm;t hree negative charges). The binding data obtained fort he reference compounds CC4 (carrying only aN ODA-GA chelator and no dye;I C 50 of 21.48 AE 1.20 nm)a nd CC5 (carryingn either chelator nor dye;I C 50 of 16.64 AE 1.06 nm)s upport the conclusions drawn before.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…This conclusion is supported by the GRPR affinity datat hat were obtained for the ICG-comprising bioconjugates CC1-CC3 and the reference compounds CC4 and CC5 [25] :A lso within the group of ICG-comprising bioconjugates CC1-CC3,astrong correlationb etween the number of negative charges of the respectived ye molecule and GRPR affinity decrease was observed, going from CC1 (27.39 AE 2.01 nm;o ne negative charge on the ICG dye) over CC2 (56.07 AE 1.47 nm;t wo negative charges) to CC3 (181.23 AE 2.24 nm;t hree negative charges). The binding data obtained fort he reference compounds CC4 (carrying only aN ODA-GA chelator and no dye;I C 50 of 21.48 AE 1.20 nm)a nd CC5 (carryingn either chelator nor dye;I C 50 of 16.64 AE 1.06 nm)s upport the conclusions drawn before.…”
Section: Resultssupporting
confidence: 54%
“…[22b] As we intended to shed light on the influence of the MIUs on the chemical, biological and photophysical properties of the resulting bioconjugates, the synthesis of appropriate reference compounds was mandatory.T hus, we furthers ynthesized 14 from 5 and 2-methyl-2-propanethiol (14 b), lacking both chelator andd ye to investigate the influence of these structure elements on the mentionedp roperties of the bioconjugates. In addition, we synthesized other reference compounds, comprising only as mall methyl-thioli nstead of the MIUs (CC5)a nd ac onjugate bearing only the NODA-GA chelator but lacking the fluorescent dye( CC4)a nd furthermore also designed bioconjugates exhibiting the same structural design as 6-13 but comprising near-infrared fluorescenti ndocyanine (ICG) dyes (CC1-CC3)( Scheme S1) (detailed data for CC1-CC5,c omprising syntheses and full characterization, are described elsewhere [25] but some resultso btained for these compounds were included here to round off the SAR analysis and to complete the picture).…”
Section: Resultsmentioning
confidence: 99%
“…To be more specific, it was found that the higher the number of negative charges in the selected dye was, the worse the resulting binding affinity to the targeted receptor. This concept was confirmed using diverse PESIN-homodimer conjugates presenting different dye units [20,21], as well as with a PESIN-homotetramer conjugate, being characterized by a higher peptide valency [22]. In this latter case, it was interestingly observed that the adverse influence of the negatively charged synthons on the target receptor affinity was in part compensated by the higher number of peptide units in the molecule, arguing a possible intramolecular spatial shielding effect of the peptides on the adverse charges.…”
Section: Introductionmentioning
confidence: 71%
“…The molecular design of the MIUs was based on the structure of the previously reported PESIN-homodimer conjugates, in which the imaging synthons were composed of (1,4,7-triazacyclononane-4,7-diyl)diacetic acid-1-glutaric acid (NODA-GA) as chelating agent for 68 Ga-or 64 Cu-labeling, a variety of fluorescent small dye molecules for the optical detection and a thiol functional group for the efficient conjugation to the peptide vector [20,21]. In the present work, a pyrylium dye (Scheme 2A, 4) [31], dansyl chloride (Scheme 2A, 5) and a cyanine dye based on the structure of indocyanine green (Scheme 2A, 6) [32] were chosen for their biological and optical properties, as well as for their different ionic charge, whose influence on the conjugated peptide moieties should be studied.…”
Section: Synthesis Of the Hybrid Multimodal Imaging Units 7-10mentioning
confidence: 99%
See 1 more Smart Citation